(untitled) - McKinley, Michael (Boston, 2006)
From the most pedagogically sound organization to the exceptional art, to the complete integration of the text with embryology, McKinley has formed a teaching system that will both motivate and enable students to understand and appreciate the wonders of human anatomy. This distinctive text was developed to stand apart from all other anatomy texts with an unrivaled, brilliantly rendered art program and a student friendly, accessible writing style that has been acclaimed by reviewers.
Keywords: Human anatomy,Giải phẫu người